Effect of fatigue on tropical wood species - Carvalho, Johnny Soares; Christoforo, André Luis; Lahr, Francisco Antonio Rocco; Aquino, Vinicius Borges de Moura (Ambiente Construído, 2022)
The aim of present study was to create a theoretical model that allowed, with security and reliability, to obtain values of strength and stiffness to which the structural element will be submitted throughout its useful life. The effect was studied for strength and stiffness properties, and the modulus of elasticity (EM) and bending strength (fM) on static bending test were evaluated according to the increasing number of cycles of the fatigue test for the five classes of hardwoods, recommended by NBR 7190 Standard Code. A reduction in strength and stiffness properties was observed with increasing loading Ncycles applied at two frequency levels. From the multivariate regression models and the respective determination coefficients, a generic model was obtained for the set involving the five wood species, emphasizing the insertion of the apparent density as an independent variable, which allowed a greater generalization of the use of the adjustments in the estimation of the EM and fM properties, presenting significant determination coefficients, ranging between 67.89% and 70.58%.